2007
DOI: 10.1007/s00467-007-0597-9
|View full text |Cite
|
Sign up to set email alerts
|

Low birth weight, but not postnatal weight gain, aggravates the course of nephrotic syndrome

Abstract: Clinical and animal studies have shown a higher risk of an aggravated course of renal disease in childhood after birth for babies small for gestational age (SGA). In addition relative "supernutrition" and fast weight gain in early infancy seem to support the development of later disease. In a retrospective analysis of 62 cases of idiopathic nephrotic syndrome treated between 1994 and 2004 at a university centre for paediatric nephrology, we related the course of disease to birth weight and to the weight gain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 51 publications
1
22
0
2
Order By: Relevance
“…Small-for-gestational age children with steroid-dependent nephrotic syndrome, for example, tend to develop a more severe course of disease (20). Likewise, it has been shown that small-for-gestational age pediatric patients with IgA nephropathy are at higher risk of developing chronic renal failure (21).…”
Section: Discussionmentioning
confidence: 99%
“…Small-for-gestational age children with steroid-dependent nephrotic syndrome, for example, tend to develop a more severe course of disease (20). Likewise, it has been shown that small-for-gestational age pediatric patients with IgA nephropathy are at higher risk of developing chronic renal failure (21).…”
Section: Discussionmentioning
confidence: 99%
“…In various renal diseases, like membranous nephropathy in adults [27] , IgA nephropathy in children [6] , idiopathic nephrotic syndrome in children [3,4] , renal damage after urinary tract infection [28] and diabetic nephropathy [29,30] , an association between low birth weight as a marker for an unfavorable intrauterine milieu and a later aggravated course of renal disease was described. In another experimental study, infusion of advanced glycation end-products in former IUGR rats increased renal mRNA expression of profibrotic cytokines and procollagen III [31] .…”
Section: Discussionmentioning
confidence: 99%
“…N A 1.5/ V V 0.5 with k = 1 and ␤ = 1.382. Total cortex volume (V cortex ) was derived from kidney mass divided by the specific weight of the kidney (1.04 g/cm 3 ) times the volume density of the cortex. The total number of glomeruli was derived from the total volume of the renal cortex and the number of glomeruli per cortex volume: N glom = N V !…”
Section: Kidney Histologymentioning
confidence: 99%
See 1 more Smart Citation
“…Low birth weight is associated with an increased risk for short stature, insulin resistance, childhood obesity, premature adrenarche, hypertension, and renal disease (1)(2)(3). The process leading to these diseases in later child-or adulthood is called perinatal programming (4).…”
mentioning
confidence: 99%